THE RELATIONSHIP BETWEEN STUDENT’S PERCEPTIONS ON THE USE OF ANDROID-BASED LEARNING MEDIA AND SCIENCE LEARNING OUTCOMES IN 5TH GRADE OF SDN HARJATANI SERANG REGENCY - Almuslimah Inayah Romadhona; Cucu Atikah; Isti Rusdiyani (JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
AbstractThe purpose of this research was to describe and analyze the relationship between student's perceptions on the use of android-based learning media and science learning outcomes of 5th-grade students at SDN Harjatani, Serang Regency. The method used is a survey method with a quantitative approach, data collection by distributing questionnaires to students. The sample in this research was 32 students at SDN Harjatani, Serang Regency. Based on the results of the analysis, it can be seen that: There is a positive relationship  between  student’s  perceptions  of  the  use  of android-based learning media with learning outcomes at SDN Harjatani Serang Regency, this is proven by the value of rcount > rtable (0.897 > 0.3388). This shows that the better student’s perceptions of the use of android-based the learning media, the higher the learning outcomes and vice versa, the worse student’s perceptions of the use of android-based learning media, the lower student learning outcomes.Keywords: Student’s Perception; Learning Outcomes; Science